CDKL1 promotes the chemoresistance of human oral squamous cell carcinoma cells to hydroxycamptothecin. (April 2019) - Li, Keyi; Meng, Zhen; Jiang, Licheng; Xia, Chunpeng; Xu, Kai; Yuan, Daoying; Chen, Haiying; Zhang, Bin; Liu, Shuwei
Abstract: CDKL1 is a cyclin-dependent kinase-like kinase that is highly expressed in diverse types of cancer cells. However, the role of CDKL1 in the chemoresistance of oral squamous cell carcinoma (OSCC) remains largely undefined. Here, we explored the role of CDKL1 in the chemoresistance of the human OSCC cell line CAL27 to hydroxycamptothecin (HCPT). Real-time quantitative polymerase chain reaction and western blotting revealed that exposure of CAL27 cells to HCPT led to a marked increase in the expression of CDKL1 at the mRNA and protein levels. Knockdown of CDKL1 significantly suppressed cell proliferation and induced cell cycle G0/G1 phase arrest in CAL27 cells based on the results of MTT and flow cytometry assays, respectively. CAL27 cells displayed attenuated biological activity of the cell population. After treatment with HCPT, whereas CDKL1 overexpression increased the resistance to HCPT of the remaining cells. Moreover, the western blot showed that the expression of cleaved-caspase 3 and phosphorylated ataxia telangiectasia mutated proteins was upregulated by HCPT treatment in CAL27 cells. Furthermore, CDKL1 overexpression partially reversed the inhibitory effects of HCPT in CAL27 cells. These results suggest that CDKL1 overexpression decreased the chemosensitivity of OSCC cells to HCPT, indicating a potential strategic approach for reversing the HCPT resistance in human OSCC. Highlights: The role of CDKL1 in the chemoresistance of the human OSCC cell line CAL27 to hydroxycamptothecin (HCPT). Exposure of CAL27 cells to HCPT led to a marked increase in the expression of CDKL1. Attenuated proliferation activity after treatment with HCPT. CDKL1 overexpression increased the resistance to HCPT of the remaining cells. CDKL1 overexpression partially reversed the inhibitory effects of HCPT in CAL27 cells. CDKL1 overexpression decreased the chemosensitivity of OSCC cells to HCPT.